KEDUDUKAN HUKUM INTERNASIONAL DALAM PENEGAKAN HAK ASASI MANUSIA - Made Nirmala dewi Sastradi Putri (Jurnal Pacta Sunt Servanda, 2022)
This study aims to introduce and deliver in detail about the position of international law in the enforcement of human rights so that the public is able to understand human rights in terms of international law and the theoretical relationship between human rights and international law in the development of dispute resolution on human rights based on law. International. According to law, or international law, and in particular with regard to human rights issues contained in international human rights disputes that bind states in their implementation with responsibilities in upholding human rights. In the provisions of international human rights law, the concept of state responsibility refers to the state's obligation to fulfill, protect and respect internationally recognized human rights. State responsibilities arising from state violations of international law. In particular, committing violations (behavior) of Human Rights and not violating, refraining from, or committing violations of human rights. Take action that is a violation of international obligations. All countries, not only partly or partially, have an obligation to promote and protect human rights, but all countries have an obligation to uphold human rights. The research method used is a normative juridical approach, namely research in the form of library research, which is a writing method used by studying literature books, laws and regulations and research focused on examining the application of rules or regulations. norms in normative law with the data in this paper taken from primary, legal, and secondary legal materials in the form of textbooks by legal professionals. This writing uses a systematic and focused method, using law as a legal basis, and as a guide for analysis. With a series of writing activities, basically it aims to collect legal materials, which are associated with legal concepts, and the results obtained are included in the form of legal ideas.